An investigation into a locking mechanism designed for a gear-based knee joint prosthesis. Issue 1 (1st January 2020) - Tong, C. X.; Bhuiyan, M. S. H.
Abstract: Background: The knee-locking mechanism in an above-knee prosthesis is crucially important to protect the prosthesis user from sudden falling down due to unexpected disturbance while standing upright. Method : An electromagnet-based knee-locking mechanism has been designed and developed for a gear-based knee joint prosthesis prototype. The electromagnet has been controlled by a microcontroller to lock and unlock the knee joint with the help of position data detection using a gyro sensor during the thigh movement. The functionality of the locking mechanism and the overall performance of the gear-based knee joint prosthesis have been tested through experiment. Results : The proposed locking mechanism incorporated in the modified gear-based knee joint is found working well with the program coded and loaded into the microcontroller. The prosthesis prototype is observed capable of recreating the lower-limb gait cycle closer to that of a healthy individual with the developed electromagnet based locking mechanism. Conclusions : Though measuring the stability performance was not possible due to the unavailability of proper testing facility, the knee-locking mechanism has been found ensuring the safety measure of that gear-based knee joint prosthesis to some reliable extent.